In-season session training load relative to match load in professional ice hockey - Allard, P.; Martinez, R.; Deguire, S.; Tremblay, J. (The Journal of Strength and Conditioning Research, 2022)
The aim of this study was to describe match load and intensity across player positions and match periods, the distribution of pregame training load and intensity over training days before a match, by player position, and the cumulative weekly training load over a season. Fifty professional ice hockey players, which at one time or another were part of the roster for the Laval Rocket during the 2017-18 season of the American Hockey League, participated in this study. External load was monitored in every training session and match over the season using portable inertial measurement units. Data are reported in absolute and relative values to a match. Defensemen have a lower intensity during matches than forwards (-1.70 OIL/min) while load is similar across position. The first period shows a higher relative load (+5.28% relative on-ice load [OIL]) while the third has a lower relative intensity (-2.91% OIL/min). Defensemen seem to train at a systematic higher relative intensity than wingers and centers (+8.34% relative OIL/min). Finally, the weekly training load remains relatively constant throughout the season (equivalent of 3.56 ± 1.69 matches played per week). Our results support the need for player monitoring in ice hockey using an individualized approach.